Organización Contable en la Compañía “GUEVAGRUP CIA. LTDA.” de la ciudad de Loja, periodo Abril-Mayo 2022 - Armijos Yanza, Angela Nashelly (2023)
The Curricular Integration Work called: accounting organization in the company "GUEVAGRUP CIA.LTDA." of the city of Loja, period April-May 2022, a prerequisite was made to obtain the title of Bachelor of Accounting and Auditing, developed in accordance with the Academic Regime Regulations of the National University of Loja in order to publicize the situation economic-financial of the Company, in addition to serving as a source of support for future work in the accounting field. I n compliance with the stated objectives: apply the Plan and Manual of Accounts and implement the accounting process; it is derived from the scientific method for the development of the investigative body; deductive through which valid conclusions and recommendations were drawn through logical reasoning, including discussion where existing problems are evaluated with possible solutions to be practiced; analyze that analyzes the daily operations carried out by the company in the execution of the Daily Book, General Ledger, Trial Balance, Work Sheet, Adjustments and Financial Statements; and synthetic that is used for the elaboration of the preliminary sheets including the application of the Manual and Chart of Accounts. In the development of the work, an Accounting Process was implemented focused on the activities described in the Company's RUC, which began by applying the Chart of Accounts provided by the Superintendency of Companies that includes groups of Assets, Liabilities, Equity, Income, Cost of sales and production and Expenses, accounts, subaccounts and detail accounts with their respective coding, as well as the manual where each group, accounts and subaccounts used throughout the work are described, explaining the nature of each one of them, as well as the movement of its balance, the Accounting Process that begins with the lifting of the Initial Inventory where everything available to the Company at the beginning of the period is indicated in detail, the Initial Balance Sheet that summarizes the Assets, Liabilities and Net Equity, subsequently the Daily Book that records entries for materials, labor, indirect costs, cost of sales and variation was implemented; Ledgers and auxiliary books where each account of assets, liabilities, net worth, income, cost of sales and production and expenses was summarized separately with the actual balance at the cut-off date; Verification Balance where the final balances of the resulting debits and credits were listed to transfer them to the respective worksheet, until concluding with the preparation of Financial Statements, resulting in a profit of $8,454.38 for the study period.